2019
DOI: 10.1186/s41016-019-0175-6
|View full text |Cite
|
Sign up to set email alerts
|

Giant serpentine aneurysm of the internal cerebral artery and mandibular aneurysm: a case report

Abstract: Background: Giant serpentine aneurysms (GSA) originate from saccular or spindle aneurysm, dissimilar from dissected aneurysm, that are defined as partially thrombosed giant aneurysms with tortuous internal vascular channel. The clinical and neuroradiologic characteristics are clarified and the mechanism of formation and the efficacy of double stent implantation in GSA are discussed. Case presentation: An 18-year-old man presented himself with a GSA arising from the internal cerebral artery (ICA). In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In previous studies, surgical resection was typically used to treat GSAs ( Xu et al, 2016 ). Recently, endovascular occlusion has been successful in treating GSAs ( Oh et al, 2016 ; Kandemirli et al, 2018 ; Deng and Feng, 2019 ; Dao et al, 2021 ; Mizuno et al, 2021 ; Civlan et al, 2022 ). Kandemirli et al reported 15 patients from three centers who underwent aneurysm and parent artery occlusion with coiling or balloon, and improvement or resolution of symptoms without any treatment-related morbidity was achieved in 11 patients ( Kandemirli et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, surgical resection was typically used to treat GSAs ( Xu et al, 2016 ). Recently, endovascular occlusion has been successful in treating GSAs ( Oh et al, 2016 ; Kandemirli et al, 2018 ; Deng and Feng, 2019 ; Dao et al, 2021 ; Mizuno et al, 2021 ; Civlan et al, 2022 ). Kandemirli et al reported 15 patients from three centers who underwent aneurysm and parent artery occlusion with coiling or balloon, and improvement or resolution of symptoms without any treatment-related morbidity was achieved in 11 patients ( Kandemirli et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, treatment options for GSA were limited and included direct resection with or without revascularization and bypass combined with occlusion of the inflow or outflow pathways. Endovascular treatments, such as balloon or coiling occlusion of the parent artery, have been reported as alternative options to GSA treatment ( Oh et al, 2016 ; Kandemirli et al, 2018 ; Deng and Feng, 2019 ; Dao et al, 2021 ; Mizuno et al, 2021 ; Civlan et al, 2022 ). However, simply occluding the GSA without ensuing adequate circulation to the distal brain parenchyma may not be consistent with the pathological characteristics of GSA, especially in the blood vessels that supply blood to critical areas of the brain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation